THE ROLE OF DIET IN THE PREVENTION OF LIFESTYLE DISEASES: A LITERATURE REVIEW - Szymon Janczura; Bartosz Dądela; Kacper Zielonka; Natalia Śliwa; Marcin Markowski; Joanna Jasińska; Eliza Kawalska; Dominika Jakubowska; Szymon Gnitecki; Maciej Borowski (International Journal of Innovative Technologies in Social Science, 2025)
Lifestyle diseases such as obesity, type 2 diabetes, cardiovascular disease, and certain cancers are still on the rise globally due to poor diet and global adoption of the Western diet. The literature review is investigating how nutrition compounds with chronic disease, as well as both harmful dietary elements and safe diets. The article responds to the impacts of sugar-sweetened beverages, processed food, artificial food components, and red meat with attention to the preventative benefits of fiber, antioxidants, and healthy fat. Proof for diets such as the Mediterranean, DASH, plant-based, and ketogenic diets is addressed, along with their metabolic, cardiovascular, and neuroprotective benefits. This review points out the value of public health programs in encouraging healthy dietary behavior as part of chronic disease prevention.